Formal decentralisation and the imperative of decentralisation 'from below': a case study of natural resource management in Nicaragua - Larson, A.M. (2004)
This article argues that decentralization of natural resource management is a political process resisted by the central government due to the feared loss of power and/or economic resources to local governments. In Nicaragua, although the formal process of power transfers largely stagnated from 1997 to 2003, decentralization ‘from below’ continued to advance thanks to political pressure from civil society and municipal governments and the increasing legitimacy of local authority. At the same time, many municipal governments have little interest in resource management where there are few apparent economic benefits. Local governments, too, however, respond, among other things, to pressure from constituents and NGOs to take on resource management initiatives. At both levels of government, local and grassroots processes are necessary conditions to make formal decentralization democratic and responsible.